Sand based on Transcultural Nursing as a Non-Pharmacological Therapy to Increase Β-Endorphin Levels and Reduce Pain Osteoarthritis in Coastal Elderly - Mujib Hannan; Hidayat, Syaifurrahman; Yulia Wardita; Abdul Muhith; Emdat Suprayitno (Journal Of Nursing Practice, 2025)
Background: Culture Inability has an affect on the comes about of care, this may be done to supply consideration and welfare for the elderly. The marvel of inborn coastal communities with special traditions whose day by day propensities begin resting within the sand, playing within the sand, splashing on the shoreline, and giving birth within the sand. When the elderly sleep well on the sand and the HPA axis is suppressed, there is a decrease in ACTH and cortisol. Purpose: Decrease ACTH and cortisol, stimulate POMC synthesis, and increase production of β endorphins that prevents the release of substance P as a key factor in the transmission of pain signals. Methods: The study uses a quasi-experimental pre-post test control group design and includes a total of 82 elderly individuals aged 60-74 years, who experience osteoarthritis pain. The sample is divided into two groups, an experimental group of 41 individuals who sleep on the sand, and a control group of 41 individuals who sleep on mattresses. The implementation of sleeping on the sand was carried out for 30 days with a duration of 6-7 hours a day. data analysis with wilcoxon test and mann whitney test. Results: The results show that there is a significant difference with p-value (<0.05) of post-test measurements on the thirtieth day on the variable β-endorphine level and pain scale. The intervention group showed difference between the pre-test and post-test after the intervention was given, with a p-value of 0.000 (<0.05). Conclusion: The study concludes that sleeping on sand is an effective non-pharmacological therapy that can increase β-endorphin levels and reduce osteoarthritis pain in coastal elderly individuals. Transcultural nursing is able to maintain healthy behavior or sick behavior physically and psychoculturally according to cultural background. The study highlights the importance of considering the cultural background of the clients while providing nursing care.